2011
DOI: 10.1111/j.1365-3016.2010.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Discordant time trends in maternal body size and offspring birthweight of term deliveries in France between 1972 and 2003: data from the French National Perinatal Surveys

Abstract: We investigated time trends in maternal weight before and during pregnancy and in infant birthweight in France, from 1972 to 2003, using data on singleton live term births from the representative National Perinatal Surveys of 1972, 1981, 1995, 1998 and 2003 (n=8,664, 4,494, 11,445, 12,006, 12,692, respectively). Mothers were interviewed a few days after delivery and data on delivery and the newborn were extracted from hospital records. Maternal prepregnancy weight, height, body mass index and pregnancy weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
(61 reference statements)
8
24
1
5
Order By: Relevance
“…In France, birthweight increased until about 1995, and subsequently decreased thereafter. By 2003, mean birthweight among term births in France had decreased back to a level last seen in 1972 [35]. In Queensland, Australia, both birthweight and term macrosomia increased from 1988 to 2001, and subsequently dropped to 2005 [36].…”
Section: Trends In Mean Birthweight Low Birthweight and High Birthwmentioning
confidence: 99%
“…In France, birthweight increased until about 1995, and subsequently decreased thereafter. By 2003, mean birthweight among term births in France had decreased back to a level last seen in 1972 [35]. In Queensland, Australia, both birthweight and term macrosomia increased from 1988 to 2001, and subsequently dropped to 2005 [36].…”
Section: Trends In Mean Birthweight Low Birthweight and High Birthwmentioning
confidence: 99%
“…L'augmentation de l'hypotrophie persistait après prise en compte de l'évolution des caractéristiques maternelles et de la consommation de tabac [35]. Le changement de tendance actuel peut être le fait du hasard ou traduire un effet plus grand de l'augmentation de la corpulence des femmes, de la baisse de la consommation de tabac, ou d'autres facteurs, ou encore être le résultat de l'évolution de la prise en charge des retards de croissance intra-utérins.…”
Section: âGe Gestationnel Et Poids De Naissanceunclassified
“…Surkan et al also found an increase in infants born over 4.5 kg between 1992 and 2001 in Sweden [7]. However, recent literature revealed that birth weight presents a trend to slightly decrease the last decade despite the increase in weight gain during pregnancy [8][9][10]. With adult overweight, obesity, and diabetes mellitus (DM) increasing substantially over the last few decades in many countries, an impending increase in the prevalence of large infants is Review lar disease (CVD) [22,23].…”
Section: Introduction ▼mentioning
confidence: 98%